Measuring teacher sense making strategies of learning analytics: a case study. (2nd January 2017) - van Leeuwen, Anouschka; van Wermeskerken, Margot; Erkens, Gijsbert; Rummel, Nikol
ABSTRACT: Teacher orchestration of the classroom is a demanding task because of the multitude of activities and the rapid pace at which these activities occur. Teachers must constantly be aware of the activities students engage in and the progress students are making, in order to be able to make informed decisions. Recent years have seen the development of learning analytics (LA) to support teachers, in the form of interfaces that capture and visualise data about learner activities. LA are hypothesised to deliver actionable knowledge, because the provided information would enable teachers to immediately translate the information into concrete intervention of some kind. This paper provides a short discussion of the hypothesised affordances of LA for supporting teachers, and subsequently, a case study is presented in which a teacher's sense making strategies of LA were investigated within a digital environment, which enabled the teacher to monitor and regulate the activities of five collaborating groups of students. Besides automatically logged teacher behaviour, eye tracking was used to examine eye movements, and cued retrospective reporting was used to evaluate the choices and decisions made by the teacher. The case study is used to discuss directions for future research concerning learning analytics to support teachers.